Characterisation and growth kinetics studies of caffeine-degrading bacterium Leifsonia sp. strain SIU - Ibrahim, Salihu; Abd. Shukor, Mohd Yunus; Syed, Mohd Arif; Wan Johari, Wan Lutfi; Ahmad, Siti Aqlima (Springer, 2016)
Caffeine is an important naturally occurring compound that can be degraded by bacteria. Excessive caffeine consumption is known to have some adverse effects. We isolated a new bacterium from agriculture soil. The bacterium was tested for its ability to utilise caffeine as the sole carbon and nitrogen source. The isolate was Gram-negative and was identified as Leifsonia sp. strain SIU based on 16S rRNA gene sequencing. It showed 97.16 % of 0.3 g/L caffeine degradation in 48 h when caffeine was used as a sole carbon and nitrogen source. The bacterial growth and degradation at 0.3 g/L caffeine concentration occurred optimally, using 5 g/L sucrose, 0.4 g/L ammonium chloride, at a temperature between 25 and 30°C and pH of 6.0–7.0. The Luong model best describes the kinetics of the strain growth. The values for the maximum specific growth rate (μ max ), the Monod half saturation constant (K S ), the maximum substrate inhibitory concentration and n are 0.049 h−1, 0.0021 mg/L, 25.0 g/L and 1.562, respectively. These bacterial features make it an ultimate means for caffeine bioremediation. This is the first report of caffeine degradation by Leifsonia sp. strain SIU.